Data is dangerous: Comparing the risks that the United States, Canada and Germany see in data troves - Susan Ariel Aaronson (Centre for International Governance Innovation (CIGI), 2020)
From posting photos and videos to tracking physical activity, apps can do almost anything, but while they may seem like harmless fun, they may also pose a threat to personal data and national security. This paper compares the different responses of the United States, Canada and Germany to data risks posed by popular apps such as FaceApp, Facebook, Strava, TikTok and ToTok. These apps and many others store troves of personal data that can be hacked and misused, putting users (and the countries in which they live) at risk.
Keywords: 330; Data Security; Risk; Comparison; Germany; Canada; USA; Datensicherheit; Risiko; Vergleich; Deutschland; Kanada; USA